2014
DOI: 10.1111/jdv.12881
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction after the treatment of glabellar lines with Botulinum toxin type A (Speywood Unit): a multi‐centre European observational study

Abstract: Background Whilst the efficacy and safety of glabella complex treatment with botulinum toxin type A (Speywood Unit)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 15 publications
0
10
0
3
Order By: Relevance
“…81 Approximately half of the patients (252; 47.9%) had not previously received ABO in the glabellar complex, while 266 patients (50.6%) had received another BoNT-A product in their glabellar region on average 12.7 months prior to enrollment in the present study. Two different satisfaction questionnaires were used, focusing on the results after treatment and the duration of the treatment, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…81 Approximately half of the patients (252; 47.9%) had not previously received ABO in the glabellar complex, while 266 patients (50.6%) had received another BoNT-A product in their glabellar region on average 12.7 months prior to enrollment in the present study. Two different satisfaction questionnaires were used, focusing on the results after treatment and the duration of the treatment, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…This maintained level of subject satisfaction across cycles is also concordant with results reported by Ascher et al [ 15 ] from a multicenter study of two injection cycles conducted in France, in which 78% of subjects either ‘completely satisfied’ or ‘satisfied’ with treatment at 1 month following initial injection and 85.4% after a second injection cycle of abobotulinumtoxinA ( N = 50). Molina et al [ 16 ] also reported high levels of overall subject satisfaction at 3 weeks following abobotulinumtoxinA treatment for GL in a single-cycle, noninterventional study. In the present study, and similarly to Molina et al, we report high levels of satisfaction with outcomes such as comfort of treatment (93%), appearing rested (87%), aesthetic outcome (96–99%), meeting or exceeding expectations (95–98%), natural look (99–100%), looking younger (83–92%) and self-feeling improvement (93–96%) [ 10 , 16 ].…”
Section: Discussionmentioning
confidence: 98%
“…Molina et al [ 16 ] also reported high levels of overall subject satisfaction at 3 weeks following abobotulinumtoxinA treatment for GL in a single-cycle, noninterventional study. In the present study, and similarly to Molina et al, we report high levels of satisfaction with outcomes such as comfort of treatment (93%), appearing rested (87%), aesthetic outcome (96–99%), meeting or exceeding expectations (95–98%), natural look (99–100%), looking younger (83–92%) and self-feeling improvement (93–96%) [ 10 , 16 ]. There was a tendency toward higher levels of subject satisfaction in the present study, which may be due to additional improvements observed with repeat treatment with abobotulinumtoxinA.…”
Section: Discussionmentioning
confidence: 98%
“…There are several possibilities how BTA alleviates depression: cosmetic effects achieved by glabellar muscle relaxation may result in a better body image, enhanced self esteem, and elevated mood (Molina et al, 2015). However, several findings make it unlikely that this is the main mechanism of action: In the first RCT the method under investigation, i.e.…”
Section: Mechanism Of Actionmentioning
confidence: 98%